Resistance to abomasal nematodes and individual genetic variability in reindeer - Côté, Steeve D.; Stien, Audun; Irvine, R Justin; Dallas, John F; Marshall, Freda; Halvorsen, Odd; Langvatn, Rolf; Albon, Steve (Molecular Ecology, 2021)
Resistance to parasites is believed to have a widespread influence on demographic and adaptive processes. In systems where parasites impose a fitness cost on their host, heterozygotes may be selected because they are more resistant to parasites than homozygotes. Our objective was to assess the relationships between genomewide individual heterozygosity and abomasal nematode burdens in female Svalbard reindeer (Rangifer tarandus platyrhynchus) after the effects of host age, locality, season, and year had been accounted for. Samples were obtained from 306 female reindeer that were culled and genotyped at nine microsatellite loci. Reindeer in our study populations are mainly parasitized by the gastrointestinal nematodes Ostertagia gruehneri and Marshallagia marshalli. The infection intensity of each parasite differed between subpopulations, and among host age classes, seasons and years. We found no significant relationships between abomasal worm burdens, or lumen and mucosa larvae, of either O. gruehneri or M. marshalli and individual heterozygosity (or mean d(2)) alone or in interactions with host age, locality, and year. Although we analysed one of the largest data set available to date on gastrointestinal nematodes of a wild ruminant, we used a typical data set of nine genetic neutral markers that may have had low power to detect heterozygosity-fitness correlations. We conclude that the proportion of the variance in parasite resistance explained by individual heterozygosity for neutral genetic markers is low in Svalbard reindeer and in vertebrates in general, and we suggest that the candidate-gene approach might be more fruitful for further research on gene-fitness correlations.